2022
DOI: 10.3389/fimmu.2022.845209
|View full text |Cite
|
Sign up to set email alerts
|

A Link Between Mitochondrial Dysfunction and the Immune Microenvironment of Salivary Glands in Primary Sjogren’s Syndrome

Abstract: BackgroundPrimary Sjogren’s syndrome (pSS) is a slowly progressive, inflammatory autoimmune disease characterized by lymphocytic infiltration into salivary and lacrimal glands. It becomes more recognized that morphology alterations of epithelial mitochondria are involved in altered cellular bioenergetics in pSS patients. The integrated analysis of the mitochondrial role in the pathogenesis and aberrant immune microenvironment in pSS remains unknown.MethodsThe mitochondria-related genes and gene expression data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 53 publications
0
32
1
Order By: Relevance
“…However, in contrast with our results, a recent study reported that MFF and MFN1 are downregulated in labial salivary gland samples of Chinese SS patients stratified in different stage groups [ 34 ]. These conflicting results could be due to the different tissue investigated in the Chinese study and the particular severe phenotype analyzed.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast with our results, a recent study reported that MFF and MFN1 are downregulated in labial salivary gland samples of Chinese SS patients stratified in different stage groups [ 34 ]. These conflicting results could be due to the different tissue investigated in the Chinese study and the particular severe phenotype analyzed.…”
Section: Discussioncontrasting
confidence: 99%
“…CMPK2 (Cytidine/uridine monophosphate kinase 2) is a thymidylate kinase, known to be associated with mitochondrial DNA (mtDNA) synthesis, and may attenuate the severity of acute respiratory distress syndrome (ARDS), a common complication of severe COVID-19, by rate-limiting for mtDNA synthesis ( 34 , 35 ). In pSS samples, CMPK2 was reported to be upregulated and was linked to the extent of immune cell infiltration, mitochondrial respiratory chain complexes, and mitochondrial metabolic pathways ( 36 ). HERC5 (HECT and RLD domain containing E3 ubiquitin protein ligase 5) is an antiviral immune protein which is induced by interferon.…”
Section: Discussionmentioning
confidence: 99%
“…mitochondrial metabolic pathways (36). HERC5 (HECT and RLD domain containing E3 ubiquitin protein ligase 5) is an antiviral immune protein which is induced by interferon.…”
Section: B Amentioning
confidence: 99%
“…Damaged mitochondria produced more reactive oxygen species than healthy mitochondria, and the presence of mitochondria in pSS salivary gland cells resulted in severe ultrastructural changes ( 115 ). Recent scientific studies have shown that mitochondria-related differentially expressed genes (CD38, CMPK2, TBC1D9, and PYCR1) are closely related to the immune cell infiltration of salivary glands in pSS patients through real-time quantitative PCR ( 116 ).…”
Section: Regulation Of the Immune Microenvironmentmentioning
confidence: 99%